Development of Neonectria punicea Pathogenic Symptoms in Juvenile Fraxinus excelsior Trees - Karadžić, Dragan; Stanivuković, Zoran; Milanović, Slobodan; Sikora, Katarzyna; Radulović, Zlatan; Račko, Vladimír; Kardošová, Monika; Ďurkovič, Jaroslav; Milenković, Ivan (Frontiers in Plant Science, 2020)
When monitoring the state of health of Fraxinus excelsior trees, unusual symptoms were discovered within a F. excelsior plantation in Bosnia and Herzegovina. These symptoms included the appearance of necrosis and cankers in the basal parts of the trees, followed by formation of fruiting bodies, however, none of these symptoms were found in the crowns. After sampling and isolation of necrotic parts from the stem base, pathogen Neonectria punicea was isolated and identified from the characteristics of pure cultures, morphology of the fruiting bodies, and from multilocus sequencing. In field conditions, juvenile F. excelsior trees were inoculated with two N. punicea isolates obtained from the necrotic tissues of both juvenile F. excelsior and mature Fagus sylvatica trees. In both isolates, twelve months post inoculation, the lengths and widths of the necroses were significantly larger compared to the control. Necroses of significantly larger lengths, widths and surfaces were found again in both tested isolates twenty-four months post inoculation. In the case of the F. excelsior isolate, the lengths of the necroses at both the stem base and at breast height increased by 1.6 times, whereas the F. sylvatica isolate increased in size by up to 1.7 and 1.8 times, respectively. Trees inoculated without a previous bark wound showed no symptoms, similar to the control trees. Scanning electron microscopy and X-ray micro-computed tomography imaging revealed that N. punicea hyphae penetrated from the cankers to the woody outermost annual growth ring and that hyphae were present mostly in the large earlywood vessels and rarely in the axial parenchyma cells. Hyphae also spread radially through the pits in vessels. The infected trees responded with the formation of tyloses in the vessels to prevent a rapid fungal spread through the axial vascular transport pathway. The ability of N. punicea to cause necroses in juvenile ash trees was demonstrated for the first time during this study. It poses a serious threat to planted forests and natural regenerations of F. excelsior especially if F. sylvatica is considered as a possible inoculum reservoir for future infections. This pathogen should be integrated within future ash resistance or breeding programs.